Survey of Insomnia and Related Social Psychological Factors Among Medical Staff Involved in the 2019 Novel Coronavirus Disease Outbreak - Zhang, Chenxi; Yang, Lulu; Liu, Shuai; Ma, Simeng; Wang, Ying; Cai, Zhongxiang; Du, Hui; Li, Ruiting; Kang, Lijun; Su, Meilei; Zhang, Jihui; Liu, Zhongchun; et al. (Frontiers in Psychiatry, 2020)
Objective: The outbreak of the 2019 novel coronavirus disease (COVID-19) caused not only extraordinary public health concerns but also tremendous psychological distress, particularly among medical staff. We aimed to investigate the prevalence rate of insomnia and confirm the related social psychological factors among medical staff in hospitals during the COVID-19 outbreak. Method: Medical staff members in China were recruited, including frontline medical workers. The questionnaire, administered through the WeChat program, obtained demographic data and asked self-design questions related to the COVID-19 outbreak, insomnia/depressive/anxiety symptoms, and stress-related symptoms. We used logistic regression analysis to examine the associations between sociodemographic factors and insomnia symptoms. Result: There were 1,563 participants in our study. Five hundred and sixty-four (36.1%) participants had insomnia symptoms according to the Insomnia Severity Index (ISI) (total score ≥ 8). A multiple binary logistic regression model revealed that insomnia symptoms were associated with the education level of high school or below (OR = 2.69, p = 0.042, 95% CI = 1.0–7.0), occupation of doctor (OR = 0.44, p = 0.007, 95% CI = 0.2–0.8), currently working in an isolation unit (OR = 1.71, p = 0.038, 95% CI = 1.0–2.8), worry about being infected (OR = 2.30, p < 0.001, 95% CI = 1.6–3.4), perceived lack of helpfulness in terms of psychological support from news or social media with regard to COVID-19 (OR = 2.10, p = 0.001, 95% CI = 1.3–3.3), and having very strong uncertainty regarding effective disease control (OR = 3.30, p = 0.013, 95% CI = 1.3–8.5). Conclusion: Our study found that more than one-third of the medical staff suffered from insomnia symptoms during the COVID-19 outbreak. The related factors included education level, an isolation environment, psychological worries about the COVID-19 outbreak, and occupation of doctor. Interventions for insomnia among medical staff are needed considering the different sociopsychological factors.